DEVELOPING SCIENCE MODULE OF PROBLEM-BASED LEARNING TO IMPROVE CRITICAL THINKING SKILL - Handayani Kusuma Pertiwi (Physics and Science Education Journal (PSEJ), 2022)
This study aims to produce a feasible science module of Problem Based Learning (PBL) to improve students' critical thinking skills and analyze the effectiveness of science learning with science module of PBL in improving students' critical thinking skills at 2 Wates JHS. The method used is Research and Development (R&D) referring to the Four-D (4D) development model with a pre-experimental one-shot case study design. The research using purposive sampling obtained subjects were 31 students of class VII D. The instruments used were validation sheets, student response questionnaires, learning implementation observation sheets, and critical thinking test. The technique of analyzing the feasibility for the science module is the conversion of quantitative scores into qualitative, four categories. While analysis technique for the effectiveness of the module is paired sample t-test and N-gain score. The results showed that the science module of PBL to improve critical thinking skills was feasible in very good category and the effectiveness of science learning using science module of PBL was effective in improving students' critical thinking skills, with a significance value of Sig(2-tailed) showing (p= 0.000 <0.05) and the N-gain value is 0.37 in medium category.